Pendekatan Berbasis Genre pada Guru Sekolah Dasar di Desa Jahiang, Kecamatan Salawu, Tasikmalaya - Yustika Nur Fajriah; Lucky Rahayu Nurjamin; Rajji Koswara Adiredja (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2019)
Departing from a case that Elementary school teachers in Jahiang village still have difficulties in supporting the government’s literacy program, GLS (Gerakan Literasi Sekolah), this study is addressed to develop those teachers’ skills in teaching texts through a workshop, focusing on the socialization of Genre-Based Approach implementation in Elementary school level. Specifically, this workshop was followed by twenty elementary schools from four schools and guided by three trainers. The method used in this workshop is lecturing, combined with small and whole class discussion, as well as a demonstration. As the conclusion, this workshop could help the teachers in designing some activities in teaching texts under Genre-Based Approach framework.